Welding cooling rate effects on microstructure of an API 5l x100 steel - de Freitas, Diego; Machado, Ivan; Mazzaferro, José; Gonzalez, Arnaldo; Mazzaferro, Cintia (International Journal of Engineering and Technology, 2016)
The aim of this work was to investigate the influence of five different cooling rates on properties of weld metal (WM) and heat affected zone (HAZ) of an API 5L X100 steel welded by GMAW. Bead on pipe (BOP) welds were made on 100x300 mm sections of a 15.8 mm thickness and 580 mm outside diameter API 5L X100 pipe, through five preheat temperatures (-30, 34, 100, 150 and 200 °C), aiming to obtain different cooling rates. Thermocouples were used to obtain the cooling time from 800 to 500 ºC (Δt8/5) during welding. The microstructures of base metal (BM) and HAZ were analyzed by light microscopy and scanning electron microscopy (SEM). Hardness measurements were made on the BOP welds in order to identify maximum and minimum values. As expected, due to the different cooling rates during welding, the distinct preheat temperatures have influenced the weld properties. Maximum and minimum HAZ microhardness, and weld metal hardness decrease as the preheat temperature increases. HAZ area, grain size of fine grained HAZ and coarse grained HAZ increase with increasing preheat temperature.